2014
DOI: 10.2319/090213-643.1
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine ligand 2 in the trigeminal ganglion regulates pain induced by experimental tooth movement

Abstract: Objective: To test the hypothesis that the chemokine ligand 2/chemokine receptor 2 (CCL2/ CCR2) signaling pathway plays an important role in pain induced by experimental tooth movement. Materials and Methods: Expression of CCL2/CCR2 in the trigeminal ganglion (TG) was determined by Western blotting 0 hours, 4 hours, 1 day, 3 days, 5 days, and 7 days after tooth movement. CCL2 localization and cell size distribution were revealed by immunohistochemistry. The effects of increasing force on CCL2 expression and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…And, exposure to MCP-1 induces an increase in intracellular calcium concentration in 5.8 to 7.9% of acutely dissociated DRG neurons from control rats [14]. Finally, recombinant MCP-1 induces a dose-dependent increase in markers of neuronal activation (Fos) in cultured trigeminal ganglion neurons, which is sensitive to a CCL2 neutralizing antibody [65]. These observations support the suggestion that functional CCR2 is constitutively expressed in sensory neurons.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…And, exposure to MCP-1 induces an increase in intracellular calcium concentration in 5.8 to 7.9% of acutely dissociated DRG neurons from control rats [14]. Finally, recombinant MCP-1 induces a dose-dependent increase in markers of neuronal activation (Fos) in cultured trigeminal ganglion neurons, which is sensitive to a CCL2 neutralizing antibody [65]. These observations support the suggestion that functional CCR2 is constitutively expressed in sensory neurons.…”
Section: Discussionmentioning
confidence: 71%
“…While there is no consensus regarding the subpopulation of nociceptors expressing CCR2 [13; 66], it is not expressed by dorsal horn neurons [66]. While, some studies have failed to detect the expression of CCR2 [14; 37; 38; 50], others have provided evidence by means of Western blot [61; 65] and immunofluorescence [8; 13; 66; 68] that CCR2 is constitutively expressed in DRG neurons of naïve rats. Furthermore, in vitro electrophysiological studies performed in DRG neurons obtained from control rats have shown that MCP-1, but not vehicle, activates between 6 to 10% of those neurons [57; 62].…”
Section: Discussionmentioning
confidence: 99%
“…Following orthodontic pain, numerous molecules are upregulated in the trigeminal ganglia, for example, P2X3 and CGRP. 61 , 62 , 63 , 64 These molecules change the biological characteristics of trigeminal neurons, for example, increased excitability. 65 With increased excitability, trigeminal neurons are more readily stimulated, resulting in thermal and mechanical hyperalgaesia.…”
Section: Neural Circuits and Regulation Of Orthodontic Painmentioning
confidence: 99%
“…Although the relevance of CCR2 in nociceptive processing is well established [6], the demonstration of the presence of these receptors in peripheral nerves remains elusive probably due to a low level of expression, the difficulty to detect them in small structures, or a limited distal transport [7]. Nevertheless, CCR2 mRNA expression has been demonstrated in dorsal root ganglia (DRG) cells of rodents [8], and CCR2 protein has been also detected in rat DRG by both immunohistochemical [7,8] and Western blot [9,10] assays. Although it has been suggested that CCR2 expression could be predominant in smalldiameter DRG cells probably corresponding to nociceptors [7], other authors describe that their presence is similar in medium and large DRG neurons [11].…”
Section: Introductionmentioning
confidence: 99%